Current Status of Wound Dressing Research in Biomaterials - Yang, Yang (International Journal of Natural Resources and Environmental Studies, 2024)
Skin is the body's first defense against external injuries, in daily production life, skin as an organ is easily injured, forming surface trauma. Wound dressings play a pivotal role in the process of skin wound repair. In order to meet the clinical demand for wound dressings, functional wound dressings with excellent biocompatibility, excellent antimicrobial activity, absorption of wound exudate and promotion of wound tissue repair have been developed. We categorize wound dressings into traditional medical dressings and novel medical wound dressings, and review the wound dressings included in the latter in terms of types, preparation methods, and effects. In future treatments for chronic wounds, researchers will integrate and utilize the antimicrobial activity, biocompatibility, and mechanical properties of wound dressings to investigate advanced wound dressings with multiple functions.